Answer:
[tex]cos(-\theta) = -0.73[/tex]
Step-by-step explanation:
It is given that:
[tex]sin(\theta -\dfrac{\pi}{2}) = 0.73[/tex]
Formula to be used:
[tex]1.\ sin(-x) = -sinx\\2.\ sin(\dfrac{\pi}{2}-x) = cosx\\3.\ cos(-x) = cosx[/tex]
Using Formula (1) written above:
[tex]\Rightarrow sin (\theta - \dfrac{\pi}{2})=sin(-(\dfrac{\pi}{2}-\theta ))\\\Rightarrow -sin(\dfrac{\pi}{2}-\theta)[/tex]
Now, using Formula (2) written above:
[tex]\Rightarrow -sin(\dfrac{\pi}{2}-\theta) = -cos \theta[/tex]
So, we can say that:
[tex]sin(\theta -\dfrac{\pi}{2}) = -cos\theta = 0.73 ...... (1)[/tex]
We have to find the value of [tex]cos(-\theta)[/tex].
Using Formula (3) written above:
[tex]cos(-\theta) = cos\theta[/tex]
So, ultimately we need to find the value of [tex]cos\theta[/tex]
Using equation (1):
[tex]-cos\theta = 0.73\\\Rightarrow cos\theta = -0.73[/tex]
So, the answer is [tex]cos(-\theta) = -0.73[/tex].